Tactics for Treating Thoracic Aortic Aneurysms using Hybrid and Endovascular Techniques in Patients with Concomitant Coronary Heart Disease - Zhekov, Ihor I.; Kravchenko, Vitalii I.; Sarhosh, Oleh I.; Osadovska, Iryna A.; Rudenko, Anatoliy V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The presence of ischemic heart disease (IHD) in patients with aortic dissection increases the risk of intraoperative and postoperative complications during aortic repair. Researches on the effect of IHD on the treatment outcomes of patients with type B aortic dissection have not been carried out often. Only single publications based on relatively small statistical material are devoted to this problem in the literature. The cohort of patients with aortic dissection and IHD is extremely complex, and surgical correction of this comorbid condition is still a controversial topic. The aim. To analyze the impact of IHD with prior correction of coronary artery lesions on the results of hybrid and endovascular treatment of patients with thoracic aortic aneurysms. Materials and methods. From 2017 to 2023, on the basis of the National Amosov Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine, 245 patients with thoracic aortic aneurysm were treated using hybrid and endovascular techniques. Of these, 14 (5.7%) patients with coronary malperfusion underwent previous cor-rection of IHD either alone or in combination with prosthetics of the aortic valve, ascending aorta and arch of the aorta, initial section of the descending aorta (elephant trunk) with a good outcome. The comparison group included 30 (12.2%) patients who underwent endovascular or hybrid correction of the descending thoracic aorta without coronary pathology. Results. In the experimental group, 5 complications (42.9%) were detected (3 in the intraoperative period and 2 in the postoperative period). The frequency of complications of a similar nature in patients without concomitant IHD (com-parison group) was 13.3%. Endoleak type 1 was also dominant in this group. In most cases, it was eliminated by balloon dilatation of the stent graft. Only in 1 case, Endoleak type 1b was the reason for re-intervention with placement of an additional stent after 6 months. Conclusions. Studies show that the presence of even corrected IHD complicates the course of endovascular and hy-brid surgical treatment of thoracic aortic aneurysms, as evidenced by significantly higher rates of postoperative compli-cations, longer length of stay in the intensive care unit, as well as time on mechanical ventilation. Preliminary myocardial revascularization in patients with IHD should be one of the main conditions for the endovas-cular treatment of aortic aneurysms, taking into account the specifics of performing such operations and the possibility of fatal complications with hemodynamically significant narrowing of the coronary arteries.